2018
DOI: 10.1029/2018jd028491
|View full text |Cite
|
Sign up to set email alerts
|

Regional Similarities and NOx‐Related Increases in Biogenic Secondary Organic Aerosol in Summertime Southeastern United States

Abstract: During the 2013 Southern Oxidant and Aerosol Study, Fourier transform infrared spectroscopy (FTIR) and aerosol mass spectrometer (AMS) measurements of submicron mass were collected at Look Rock (LRK), Tennessee, and Centreville (CTR), Alabama. Carbon monoxide and submicron sulfate and organic mass concentrations were 15–60% higher at CTR than at LRK, but their time series had moderate correlations (r ~ 0.5). However, NOx had no correlation (r = 0.08) between the two sites with nighttime‐to‐early‐morning peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 123 publications
2
19
0
Order By: Relevance
“…Similar to FT-IR-PLS, the mass recovery of organics in aerosol mass spectrometry is 75 % for O/C ratios and 91 % for H/C ratios (Aiken et al, 2008; assuming constant collection and relative ionization efficiencies with particle composition). A study comparing simultaneous characterization of OM composition found that the FT-IR spectrometry OM concentrations were 20 %-40 % lower than those observed using aerosol mass spectrometry, within the combined uncertainties of the methods (∼ 20 % for each method; Liu et al, 2018). Although TOR OC mass recovery from the filters is expected to be 100 % based on analysis of organic standards, the OC/EC split into thermal-optical carbon analysis methods may introduce uncertainty into the TOR OC concentration (Chow et al, 2004).…”
Section: Evaluating Ft-ir Measurements: Mass Recoverymentioning
confidence: 94%
See 2 more Smart Citations
“…Similar to FT-IR-PLS, the mass recovery of organics in aerosol mass spectrometry is 75 % for O/C ratios and 91 % for H/C ratios (Aiken et al, 2008; assuming constant collection and relative ionization efficiencies with particle composition). A study comparing simultaneous characterization of OM composition found that the FT-IR spectrometry OM concentrations were 20 %-40 % lower than those observed using aerosol mass spectrometry, within the combined uncertainties of the methods (∼ 20 % for each method; Liu et al, 2018). Although TOR OC mass recovery from the filters is expected to be 100 % based on analysis of organic standards, the OC/EC split into thermal-optical carbon analysis methods may introduce uncertainty into the TOR OC concentration (Chow et al, 2004).…”
Section: Evaluating Ft-ir Measurements: Mass Recoverymentioning
confidence: 94%
“…1; Table 1). Mass contributions from organic S and N comprise a smaller portion of ambient OM (Liu et al, 2009;Stone et al, 2012) and were not included in this work. Substantial contributions of organosulfates to southeastern aerosol composition are possible (Hettiyadura et al, 2015), and the OM/OC ratios of small organosulfate molecules are high; therefore, future models may consider such chemicals.…”
Section: Chemicals Used In the Calibration Models To Concisely Represmentioning
confidence: 99%
See 1 more Smart Citation
“…"A study comparing simultaneous characterization of OM composition found that the FT-IR spectrometry OM concentrations were 20-40% lower than those observed using aerosol mass spectrometry, within the combined uncertainties of the methods (∼20% for each method; Liu et al, 2018)." 6.…”
Section: C4mentioning
confidence: 98%
“…Multiple FGs are present in every molecule, so the contributions of FGs to each sample are indicative of OM composition; a greater fraction of oxygenated FG content can indicate more aged material (Chhabra et al, 2011;Moretti et al, 2008). By studying the FG composition of OM within atmospheric aerosol samples, patterns emerge in the bulk OM composition, from which sources and formation processes can be revealed (Corrigan et al, 2013;Liu et al, 2018;Russell et al, 2009;Takahama et al, 2011). The Yorkville, Georgia (YRK) site was located ~55 km from a major urban area (Atlanta), and was surrounded by pastures and nearby forest (~100-300 m from samplers).…”
Section: Introduction 1a Functional Group Perspective On Atmospheric Aerosol Organic Mattermentioning
confidence: 99%